A scenario for the conversion of Common Agricultural Policy payments in Spain after the 2011 legislative proposals - Andrés,Silvia (Pontificia Universidad Católica de Chile. Facultad de Agronomía e Ingeniería Forestal, 2013)
S. Andrés, J.M. García, and R. Compés. 2013. A scenario for the conversion of Common Agricultural Policy payments in Spain after the 2011 legislative proposals. Cien. Inv. Agr. 40(2):291-306. This paper evaluates the impact of a new model of agricultural policy outlined in legislative proposals issued by the European Commission in October 2011 and estimates its effects on agricultural aid in Spanish Autonomous Communities compared with 2009. Therefore, the OECD agricultural policy-index system was used. To the extent that transversal criteria are applied, which support the transfer of aid between territories, the results suggest that changing the payment assignation model would involve a redistribution of aid towards areas that currently least benefit from them.